STUDI KUALITATIF TENTANG RESPONS MASYARAKAT TERHADAP PASIEN COVID-19 DI KELURAHAN PERIUK - Mudattiiles, Siti Min; Susilowati, Yuni; Winarni, Lastri Mei (Nusantara Hasana Journal, 2022)
This research is a qualitative research with descriptive method. The subject of this research is the community in Periuk Village. The data collection method used in this research is the method of interview (interview), observation, and documentation. This research was conducted on seven respondents who live in Periuk Village. The purpose of this research is to find out the community's insight regarding covid-19, the response that arises among the community when they hear things related to covid-19 and covid-19 patients. The background to the problem in this research is that many of our people still lack insight into COVID-19 and the negative responses that people make when they hear about Covid-19 patients in their area. The conclusions of the research results obtained are: first, the majority of people in Periuk Village already have sufficient insight about covid-19. Second, the majority of the responses that arise among the community towards Covid-19 patients are very good. Third, there is a sense of caring for each other, mutual help from the community for people with COVID-19 while still carrying out the protocols that have been recommended by the government.